Organic substitutions improve soil quality and maize yield through increasing soil microbial diversity. (1st May 2022) - Liu, Hanwen; Du, Xiaofang; Li, Yingbin; Han, Xu; Li, Bing; Zhang, Xiaoke; Li, Qi; Liang, Wenju
Abstract: Organic substitution is beneficial to sustainable agricultural development. In order to determine the proper fertilization strategy, it is necessary to evaluate the effects of partial substitution of nitrogen fertilizer with organic amendments on soil quality and crop yield, as well as their decisive factors. A five-year organic substitution field experiment was set up to investigate the effects of partial substitution of chemical fertilizer with stover, cattle manure and biochar on soil quality, soil microbial and nematode diversities and crop yield in a maize ( Zea mays L.) field of Northeast China. Our results showed that organic substitutions increased soil quality and manure substitution increased maize yield through changing the composition and functional group of soil biota. Bacteria played important roles in determining the maize yield, but the beneficial effects were contingent on the different types of organic substitution. Stover substitution improved soil quality through increasing bacterial diversity but may lead to the competition of nitrogen between microorganisms and crops. Compared with conventional fertilization, manure substitution provided resources with suitable C/N ratio (6.82) and resulted in the higher maize yield, but the soil quality improvement was weaker under manure substitution than under stover substitution. Biochar substitution reduced the relative abundance of plant-parasitic nematodes but caused an increasing of potential pathogenic fungi for maize. Comprehensively, stover substitution is the most promising fertilization regime for maize in Northeast China from the perspective of soil quality and soil biodiversity. Highlights: Organic substitution increased soil quality through increasing bacterial diversity. Manure substitution increased maize yield due to the suitable C/N. Bacterial functional group played important roles in determining the maize yield.